Adaptive c-chart with estimated parameter. Issue 1 (2nd January 2017) - Keyvandarian, Ali; Noorossana, R.; Hashemian, S. Mohammad; Maryam, Shekary A.
ABSTRACT: In the design of control charts, it is usually assumed that process parameters are known. However, in many practical applications the values of these parameters are unknown and should be estimated using historical in-control process observations. In this study, the performance of adaptive c-chart with estimated parameter is evaluated. It is demonstrated that by increasing the size and the number of samples in estimating the process parameter, the performance of the chart converges to that of the known parameter case. Finally the best phase I sampling scenarios are presented to make the chart with the estimated parameter perform as well as the chart with the known parameter.